Biogenic volatile organic compound emissions along a high arctic soil moisture gradient - Svendsen, Sarah Hagel; Lindwall, Frida; Michelsen, Anders; Rinnan, Riikka (The Science of the total environment, 2016)
Emissions of biogenic volatile organic compounds (BVOCs) from terrestrial ecosystems are important for the atmospheric chemistry and the formation of secondary organic aerosols, and may therefore influence the climate. Global warming is predicted to change patterns in precipitation and plant species compositions, especially in arctic regions where the temperature increase will be most pronounced. These changes are potentially highly important for the BVOC emissions but studies investigating the effects are lacking. The aim of this study was to investigate the quality and quantity of BVOC emissions from a high arctic soil moisture gradient extending from dry tundra to a wet fen. Ecosystem BVOC emissions were sampled five times in the July-August period using a push-pull enclosure technique, and BVOCs trapped in absorbent cartridges were analyzed using gas chromatography–mass spectrometry. Plant species compositions were estimated using the point intercept method. In order to take into account important underlying ecosystem processes, gross ecosystem production, ecosystem respiration and net ecosystem production were measured in connection with chamber-based BVOC measurements. Highest emissions of BVOCs were found from vegetation communities dominated by Salix arctica and Cassiope tetragona, which had emission profiles dominated by isoprene and monoterpenes, respectively. These results show that emissions of BVOCs are highly dependent on the plant cover supported by the varying soil moisture, suggesting that high arctic BVOC emissions may affect the climate differently if soil water content and plant cover change. [Display omitted] •Biogenic volatile organic compound (BVOC) emissions from the Arctic are poorly understood•We assessed BVOC emissions over a soil moisture gradient in the High Arctic•BVOC measurements were coupled with CO2 exchange, vegetation and soil analyses•BVOC emissions were dependent on the vegetation composition controlled by soil moisture